7 Records of the Colony of Rhode Island and Providence Plantations, in New England 567 (1862) - (:unkn) unknown (My University, 1776)
Required any male citizen age sixteen or above to take a loyalty oath and failure to do so without providing proper justificaiton results in disarmament
Keywords: POSSESSION - DANGEROUS PERSONS